Gallic acid ameliorates dextran sulfate sodium-induced ulcerative colitis in mice via inhibiting NLRP3 inflammasome - Yu, Tian-Yuan; Feng, Yi-Ming; Kong, Wei-Song; Li, Shan-Ni; Sun, Xue-Jiao; Zhou, Gui; Xie, Rui-Fang; Zhou, Xin (Frontiers in Pharmacology, 2023)
Background: Ulcerative colitis (UC) is a chronic recurrent inflammatory bowel disease (IBD). The conventional drugs for UC may induce severe side effects. Herbal medicines are considered as a complement and alternative choice for UC. Purpose: To estimate the effect of natural polyphenol gallic acid (GA) on NLRP3 inflammasome with dextran sulfate sodium (DSS)-induced colitis in mice. Study design: Body weights and symptoms of Balb/c mice were recorded. Histological evaluation, ELISA, q-PCR, immunohistochemistry, and western blotting were respectively carried out to observe morphology, cytokine contents, mRNA expressions and protein expressions. Lipopolysaccharide (LPS)-induced RAW264.7 macrophage was exploited to probe GA’s effect on relative protein expression. Results: GA attenuated weight loss (P<0.05), relieved symptoms and ameliorated colonic morphological injury (P<0.05) of mice induced by DSS. GA also declined contents of TNF-α, IL-1β, IL-18, IL-33 and IFN-γ in serum and colon of mice elevated by DSS, down-regulated protein and mRNA expressions of NLRP3 pathway in colon tissue. Further, GA down-regulated expressions of NLRP3 (P<0.05), iNOS (P<0.01), COX2 (P<0.01) and P-p65 (P<0.05) and suppressed NO release (P<0.001) in LPS-induced RAW264.7 cell. Conclusion: GA ameliorated DSS-induced UC in mice via inhibiting NLRP3 inflammasome. These findings furnish evidence for the anti-inflammatory effect of herbal medicines containing GA on UC.